Regulatory T cell enhancement in adults with cystic fibrosis receiving Elexacaftor/Tezacaftor/Ivacaftor therapy - Westhölter, Dirk; Raspe, Jonas; Uebner, Hendrik; Pipping, Johannes; Schmitz, Mona; Straßburg, Svenja; Sutharsan, Sivagurunathan; Welsner, Matthias; Taube, Christian; Reuter, Sebastian (Frontiers in Immunology, 2023)
Cystic fibrosis (CF), especially CF lung disease, is characterized by chronic infection, immune dysfunction including impairment of regulatory T cells (Tregs) and an exaggerated inflammatory response. Cystic fibrosis transmembrane conductance regulator (CFTR) modulators have shown to improve clinical outcomes in people with CF (PwCF) with a wide range of CFTR mutations. However, it remains unclear whether CFTR modulator therapy also affects CF-associated inflammation. In this longitudinal observational study, peripheral blood mononuclear cells and plasma were collected before and at three and six months after the initiation of elexacaftor/tezacaftor/ivacaftor therapy; systemic cytokines and lymphocyte subsets were determined using flow cytometry. Elexacaftor/tezacaftor/ivacaftor therapy was initiated in 77 PwCF and improved percent predicted FEV1 by 12.5 points (p<0.001) at 3 months. During elexacaftor/tezacaftor/ivacaftor therapy, percentages of Tregs were enhanced (+18.7%, p<0.001), with an increased proportion of Tregs expressing CD39 as a marker of stability (+14.4%, p<0.001). Treg enhancement was more pronounced in PwCF clearing Pseudomonas aeruginosa infection. Only minor, non-significant shifts were observed among Th1-, Th2- and Th17-expressing effector T helper cells. These results were stable at 3- and 6-month follow-up. Cytokine measurements showed a significant decrease in interleukin-6 levels during treatment with elexacaftor/tezacaftor/ivacaftor (–50.2%, p<0.001). In conclusion, treatment with elexacaftor/tezacaftor/ivacaftor was associated with an increased percentage of Tregs, especially in PwCF clearing Pseudomonas aeruginosa infection. Targeting Treg homeostasis is a therapeutic option for PwCF with persistent Treg impairment.